1998
DOI: 10.1007/s00585-998-0589-5
|View full text |Cite
|
Sign up to set email alerts
|

The role of vibrationally excited oxygen and nitrogen in the ionosphere during the undisturbed and geomagnetic storm period of 6-12 April 1990

Abstract: Abstract. We present a comparison of the observed behavior of the F-region ionosphere over Millstone Hill during the geomagnetically quiet and storm periods of 6±12 April 1990 with numerical model calculations from the IZMIRAN time-dependent mathematical model of the Earth's ionosphere and plasmasphere. The major enhancement to the IZMIRAN model developed in this study is the use of a new loss rate of O 4 S ions as a result of new high-temperature¯owing afterglow measurements of the rate coe cients u 1 and u 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
66
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(69 citation statements)
references
References 50 publications
3
66
0
Order By: Relevance
“…However, the reaction rates for both O 2 and N 2 may be a ected by vibrational excitation (e.g. Pavlov, 1998), though not necessarily in the same way.…”
Section: Complicationsmentioning
confidence: 99%
“…However, the reaction rates for both O 2 and N 2 may be a ected by vibrational excitation (e.g. Pavlov, 1998), though not necessarily in the same way.…”
Section: Complicationsmentioning
confidence: 99%
“…(4). Pavlov (1998) found that during the undisturbed and geomagnetic storm periods at middle latitudes at moderate solar-activity conditions deviation from a Boltzmann distribution of O 2 v was large at the vibrational energy levels v b 3 and close to a Boltzmann distribution of O 2 v for v 1Y 2Y and 3. The main contribution to vv 0 arising from the deexcitation of O 2 v is brought by the deexcitation of O 2 1 and O 2 2X As a result, it is possible to use a Boltzmann distribution of O 2 v in calculations of vv 0 as…”
Section: Introductionmentioning
confidence: 87%
“…The number density of vibrationally unexcited O 2 is much larger than the number density of vibrationally excited O 2 during the undisturbed and geomagnetic storm periods at middle latitudes (Pavlov, 1989(Pavlov, , 1994(Pavlov, , 1998. As a result, the collisions of thermal electrons with vibrationally unexcited O 2 yield the main contribution to v vib O 2 and the possible error of Eq.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations